Immune response to shiga toxin producing Escherichia coli : detection of antibodies against outer membrane proteins of the bacteria in healthy population of Bangladesh - Mirza, Nahreen (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Masters of Science in Biotechnology, 2015.